Impact of an alternative chromosome 17 probe and the 2013 American Society of Clinical Oncology and College of American Pathologists guidelines on fluorescence in situ hybridization for the determination of HER2 gene amplification in breast cancer. Issue 12 (13th February 2017) - Donaldson, Alana R.; Shetty, Shashirekha; Wang, Zhen; Rivera, Christine L.; Portier, Bryce P.; Budd, G. Thomas; Downs‐Kelly, Erinn; Lanigan, Christopher P.; Calhoun, Benjamin C.
Abstract : BACKGROUND: The dual‐probe fluorescence in situ hybridization (FISH) assay for human epidermal growth factor receptor 2 ( HER2 ) gene amplification in breast cancer provides an HER2 : CEP17 (centromere enumeration probe for chromosome 17) ratio. Copy number alteration (CNA) in CEP17 may skew this ratio. The authors analyzed the impact of the 2013 American Society of Oncology/College of American Pathologists (ASCO/CAP) guidelines and an alternative chromosome 17 probe on HER2 status in tumor specimens with CEP17 CNA. METHODS: Specimens with CEP17 CNA (n = 310) were selected from 3048 tumor samples that were received from January 2013 to June 2015 for testing with the alternative chromosome 17 probe D17S122 . Reclassification of HER2 status was assessed using the 2007 and 2013 ASCO/CAP guidelines. RESULTS: The alternative chromosome 17 probe reclassified 82 of 310 (26.5%) and 87 of 310 (28.1%) tumors using the 2007 and 2013 guidelines, respectively. Of the 41 of 310 tumors (13.2%) that were reclassified from nonamplified to amplified according to 2007 guidelines, 28 of 41 (68.3%) had an average HER2 copy number ≥4.0 and <6.0. The 39 of 310 tumors (12.6%) that were reclassified from equivocal to amplified according to 2013 guidelines had a mean HER2 copy number between ≥4.0 and <6.0. Most of these patients had stage I, hormone receptor‐positive, lymph node‐negative tumors, which is an unusual clinicopathologic profile for HER2 ‐amplified tumors, and most received HER2 ‐targeted therapy in addition to endocrine therapy. CONCLUSIONS: Reflex testing with an alternative chromosome 17 probe using the 2013 ASCO/CAP guidelines reclassified 28.1% of tumor samples that had CEP17 CNA, converting nearly one‐half from equivocal to amplified. The benefit of HER2 ‐targeted therapy in this patient population requires further study. Cancer 2017;123:2230–2239. © 2017 American Cancer Society . Abstract : The use of an alternative chromosome 17 probe in fluorescence in situ hybridization for human epidermal growth factor receptor 2 (HER2) gene amplification in breast cancer results in the classification of more patients as eligible for HER2‐targeted therapy. The benefit these patients derive from HER2‐directed therapy is unproven.